Menurunkan Skala Nyeri Bayi Prematur melalui Facilitated Tucking disertai ‘Hadir-Berbicara’ sebagai Upaya Penerapan Teori Comfort Kolcaba - Nopi Nur Khasanah; Yeni Rustina (Alma Ata University Press, 2017)
Premature infants had been experience of pain in neonatal ward that occur each day during treatment. Nurse need to do an intervention for reduce the scale of pain on premature infants. Pain management have to do at birth because of the repeated painful procedures in early life can affect the development of central nerve system permanently. The objective of this study was to describe the application of Kolcaba Comfort’s theory through facilitated tucking accompanied with ‘being with-talking to’ techniques in premature’s infant at high risk infant care. The method that used was case study by applying the four contexts of comfort’s experience associated with the three types of comfort based on Kolcaba Comfort’s theory in providing nursing care on five premature infants who have some painful procedures. The nursing intervention through facilitated tucking accompanied by ‘being with-talking to’ based on the principles of Kolcaba Comfort’s theory gave a positive result against premature infants’s comfort level. Four from five premature infants are in the level of transcendence which is a type of supreme comfort after the ease and relief. Kolcaba Comfort’s theory can be applied within the scope of neonatal care due in accordance with the developmental care of the infants and could reduce the scale of pain.